2012
DOI: 10.1080/01635581.2012.630157
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Plasma Levels of Interleukin-8 in Stage IV Non-Small-Cell Lung Cancer Patients: Relationship With Nutritional Status and Prognosis

Abstract: Interleukin (IL)-8 promotes cellular proliferation and angiogenesis in patients with non-small-cell lung cancer (NSCLC) and may be related to cachexia. Our aim was to investigate the relationship of IL-8 levels with nutritional status, and clinical outcome of patients with NSCLC. Patients with metastatic NSCLC referred for first-line therapy were eligible. Baseline IL-8 levels were measured in plasma. The Mini Nutritional Assessment (MNA) was used for the evaluation of the nutritional status, and patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Therefore, the development of potential biomarkers for these tumors is an urgent unmet need. We also observed that patients with higher IL8 levels presented decreased survival, in accordance with previous reports (25)(26)(27)29,31,(42)(43)(44). Although this fact may be explained by tumor burden, a contribution by a direct pathogenic role of IL8 cannot be excluded, because IL8 is involved in tumor vascularization (5,45) and chemotactically disorients migration of immune cells (12).…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, the development of potential biomarkers for these tumors is an urgent unmet need. We also observed that patients with higher IL8 levels presented decreased survival, in accordance with previous reports (25)(26)(27)29,31,(42)(43)(44). Although this fact may be explained by tumor burden, a contribution by a direct pathogenic role of IL8 cannot be excluded, because IL8 is involved in tumor vascularization (5,45) and chemotactically disorients migration of immune cells (12).…”
Section: Discussionsupporting
confidence: 79%
“…It is also known that high level of cytokines TNFα, IL-6, and IL-2 are associated with a decrease in food intake and may contribute to anorexia. Other studies have demonstrated the relationship between malnutrition and inflammatory markers in specific population groups, including in children [24,25], dialysis patients [14,15,18,[26][27][28][29][30], patients with neoplasms [19,31,32], and patients with autoimmune diseases [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there is an evidence of a relationship between malnutrition and inflammation expressed by elevated levels of pro-inflammatory cytokines and these biomarkers were independent risk factors of malnutrition in various disease states, such as renal failure [18], neoplastic disease [19], and Alzheimer's disease [20].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with international consensus for cachexia diagnosis, our results demonstrate systemic inflammation in cancer cachectic vs. non-cachectic patients, with increased circulating CRP, IL6, TNFα, IL8, and IL5 levels. A previous study reported that high plasma concentrations of IL8 in patients with advanced lung cancer (stage IV), were correlated with cachexia [51]. On the other hand, increased circulating levels of IL8 are also reported as markers in patients with pulmonary fibrosis [52].…”
Section: Discussionmentioning
confidence: 99%